TINGKAT PENGETAHUAN TENTANG PENCABUTAN GIGI DENGAN TINGKAT KECEMASAN PADA PASIEN PENCABUTAN GIGI POSTERIOR RAHANG BAWAH DI KLINIK DENTAL CENTER PROF. SUDIBYO YOGYAKARTA - Santi Noviana; Sri Ediati; Almujadi Almujadi (Poltekkes Kemenkes Yogyakarta, 2014)
The extractie of teeth is the easiest way and the bestmethod to missing the felling of toothache, if the nerve ofteeth has no funcion anymore or if the teeth had got infectionwhich is in very seriously condition.The extractie of theteeth can be done with the way which simply or extractiethe teeth complicatedly. Visiting the place of the practicaldentist for a half of people is something that horrified, it isprove with still alot of people who come to visit the pleaceof practical dentist after they got their cheeks or part ofbelow their eye become swollen and seriously ill whichirresistible. It is know with the increasing of science ofsomeone with the anxiety of people to extractie the teeth isdecreasing. The reason of anxiety come because of badexperience used to be with the way to cure the diseaseand ill when they got toothache in nursing of teeth.Kind ofthis research is observational with the way analizyng acondition with the way of approach, observation of collectingthe datas use of quisioners with design of cross sectionalthis research is doing in 2013. The location of researchis at Clinic Dental Center Prof. Sudibyo, age 25th -50th years who want to extractie the teeth. Technic of takingof sampling use qouta sampling that is technik of samplingwhich is taken by all the subjects that is complete tocriteria of scientist that is the patient who want to do extractiethe teeth of posterior lower jaw. Analyzis of datas use experimentof correlatoinal statistic of sparman rank. It gotcorrelational which is meaning of the level the science ofextractie the teeth with the level of anxiety to patient ofextractie the teeth of posterior lower jaw get the score whichsignificant 0,01< 0,05. The result shows the level of scienceabout the extractie 20 subjects are low criteria and 4subjects are medium criteria for anxiety of the extractie theteeth of posterior lower jaw.